Does Farmer Group Participation Affect Agricultural Insurance Adoption? Evidence from Indonesian Rice Farmers - Hartono, Rachman; Retnoningsih, Dwi; Rahman, Moh. Shadiqur; Wijayanto, Hari Wahyu (Jurnal Pembangunan dan Alam Lestari, 2023)
Although agricultural insurance plays a vital role in minimizing the potential risk of yield loss, the adoption rate among farmers in Indonesia remains low. Using cross-sectional data from the Indonesian rice farmers’ survey, this study investigates how participation in a farmer group affects the decision to adopt agricultural insurance. A recursive bivariate probit model was employed to estimate the participation’s effects on agricultural insurance adoption. The finding indicates that farmer group participation positively and significantly affects the adoption. Regarding the control variables, farmers’ experience and education drive the adoption. In contrast, age shows a negative correlation. Meanwhile, the determinants of farmer group participation are gender, access to credit, and social activity involvement. Likewise, age also negatively and significantly affects the probability of farmer group participation. These findings highlight the essential role of farmer group participation in agricultural insurance adoption. Therefore, we suggest promoting membership sign-ups among smallholder farmers Keywords: agriculture insurance, farmers group, recursive bivariate probit model, rice farmers